Comparison of efficacy of different endovascular lead extraction techniques. (25th November 2020) - Bracke, F; Verberkmoes, N; Rademakers, N; Van 't Veer, M; Van Gelder, B.M
Abstract: Background: Reports on lead extraction often concern a single technique, rendering direct comparison between techniques difficult. Purpose: We compared efficacy and complications of consecutively used endovascular extraction techniques in a single centre. Methods: Single centre observational study of consecutive lead extractions from 1997 to 2019. The preferential technique used over time was at first a laser sheath (LS), subsequently a femoral approach (FA) if feasible, and finally rotational mechanical sheaths (RMT). The FA remained the preferential initial technique for atrial and coronary sinus leads during the latter period. Extraction results are reported per lead for the initial technique before any alternative approach was initiated. Results: A total of 1725 leads (including 222 ICD) leads were extracted in 775 patients. Primary endovascular extraction was attempted in 1703 leads (median implant time 6.0 yrs. [IQR 2.7–10.2]) with the remainder being surgically removed. Traction sufficed to remove 588 leads (median implant time 2.4 yrs. [IQR 1.2 - 4.7]). The table shows the radiological and procedural success of the initially used technique per lead. Including use as backup technique there were 7.4%, 0.5% and 1.2% major complications with respectively LS, FA, and RMT. Including backup approaches, clinical success (lead completely removed or only lead fragment <4cm left behind without mayor complication) for endovascular extraction of the 1703 leads was 94.8%. Conclusion: The laser sheath has an inferior procedural outcome compared to rotational mechanical sheaths or a femoral approach which is largely the results of a higher complication rate. The femoral approach and mechanical rotational sheaths are seemingly equally effective, but the femoral approach is not suitable for many ICD leads and technically more demanding for ventricular leads. In current practice, the combination of a femoral approach and rotational mechanical sheaths yields optimal results. Funding Acknowledgement: Type of funding source: None